Ruthenium-based catalyst with high catalytic activity and preparation method thereof

By preparing a ruthenium-based catalyst Ni(OH)x-RuNC with high catalytic activity, the problems of low activity and low atom utilization of noble metal catalysts have been solved, achieving high-efficiency catalytic performance suitable for biosensing, environmental remediation and chemical synthesis.

CN121016783APending Publication Date: 2025-11-28重庆医科大学国际体外诊断研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511212850.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing precious metal catalysts have low catalytic activity and low atom utilization, which can easily lead to waste of precious metals during the preparation process. Moreover, existing technologies cannot maintain high catalytic performance while making efficient use of precious metals.

Method used

By loading highly dispersed ruthenium clusters onto nickel hydroxide nanoplates, the structure and function of the catalyst were analyzed through a series of characterization methods: ① The corresponding XRD patterns of Ni(OH)x and Ni(OH)x-RuNC are shown in Figure 2.

Benefits of technology

Highly efficient catalytic activity was achieved, and the analysis of the catalyst's structure and function was reduced: ① The corresponding XRD patterns of Ni(OH)x and Ni(OH)x-RuNC samples are shown in Figure 2. After Ru treatment, the diffraction peaks of the Ni(OH)x-RuNC catalyst still largely match the positions of Ni(OH)2·0.75H2O (JCPDS no. 00-038-0715).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016783A_ABST
    Figure CN121016783A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a ruthenium-based catalyst with high catalytic activity and a preparation method thereof. The ruthenium-based catalyst (Ni (OH) x-RuNC) with efficient catalytic activity is prepared by highly dispersing ruthenium clusters and stably loading the ruthenium clusters on a nickel hydroxide nano-plate synthesized by a hydrothermal method through a photochemical deposition strategy. The synthesis method is simple and easy to implement, and is beneficial to large-scale production and practical application and popularization; under optimized reaction conditions, the high catalytic activity of the ruthenium-based catalyst is shown as follows: the maximum reaction speed (Vmax) of Ni (OH) x-RuNC catalytic substrate H2O2 is 1047.4 * 10 <-8 > M.s <-1 >, and Km is 1995mM; the maximum reaction speed (Vmax) of the catalytic substrate TMB is 69.32 * 10 <-8 > M.s <-1 >, and Km is 0.213 mM.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of nanomaterials, and more specifically, it relates to a ruthenium-based catalyst with high catalytic activity and its preparation method. Background Technology

[0002] Catalytic nanoparticles are a class of nanomaterials with intrinsic enzyme-like catalytic activity, and have attracted much attention in the design and development of highly sensitive biosensors in recent years. Since the discovery of the inherent peroxidase-like activity of iron(III) oxide (Fe3O4) nanoparticles in 2007, researchers have been actively exploring nanomaterials with similar activities. Currently, nanomaterials with intrinsic peroxidase-like activity mainly include iron-based (such as Fe3O4 nanoparticles), noble metal-based (such as cerium oxide and platinum nanoparticles), and carbon-based (such as graphene oxide and carbon nanotubes) materials. However, the performance of most non-noble metal-based catalysts is still far inferior to that of noble metal catalysts (such as platinum, ruthenium, rhodium, and gold). Considering the scarcity and high cost of noble metals, how to reduce the amount of noble metals used and make full use of these resources when designing alternative catalysts with peroxidase-like activity remains a very challenging problem.

[0003] To enhance atomic participation in catalytic reactions, an effective approach is to shrink bulk catalysts to nanoparticles, nanoclusters, or even single atoms. Theoretically, noble metal single-atom catalysts (NMSACs) can achieve 100% atom utilization efficiency, thus meeting the demand for optimal noble metal resource utilization. However, the catalytic activity of most reported NMSACs remains lower than that of benchmark catalysts, and even less than that of conventional nanoparticle catalysts. This is primarily due to the typically low metal content (<1 wt%) in NMSACs. During the synthesis of NMSACs, attempts to increase the metal content can lead to the migration and aggregation of individual atoms into larger clusters due to their high specific surface energy. Furthermore, the preparation of NMSACs may involve additional physical or chemical treatment steps, such as acid leaching, to remove impurities and unstable nanoparticles, potentially resulting in waste of noble metals and reduced yield. Therefore, a balance must be struck between atom utilization and catalytic performance when developing noble metal catalysts with peroxidase-like activity. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention successfully constructs a ruthenium-based catalyst with high catalytic activity, wherein ruthenium (Ru) clusters are highly dispersed and stably supported on a nickel hydroxide support (Ni(OH)). x -Ru NC This catalyst exhibits excellent performance on its substrate. We further analyzed the properties of Ni(OH) using in-situ X-ray absorption spectroscopy (XAS). x -Ru NCLocal atomic structure of Ru.

[0005] Ni(OH) x -Ru NC Preparation steps:

[0006] (1) Dissolve nickel nitrate hexahydrate in a mixed solution containing triethylene glycol and water to obtain a nickel nitrate solution;

[0007] (2) The aqueous solution containing urea, sodium bicarbonate and tetrabutylammonium hydroxide is stirred and mixed with the nickel nitrate solution, transferred to a Teflon autoclave, reacted at high temperature, and washed and dried to obtain powdered nickel hydroxide nanoplates.

[0008] (3) The nickel hydroxide nanoplates are suspended in a mixed solution containing methanol and water to obtain a nickel hydroxide suspension;

[0009] (4) After dissolving ruthenium trichloride trihydrate powder, the solution was degassed with nitrogen, irradiated with ultraviolet light, washed, and freeze-dried to obtain Ni(OH). x -Ru NC .

[0010] Ruthenium clusters were loaded onto nickel hydroxide nanoplates using a photochemical deposition strategy. The structure and function of the catalyst were analyzed using a series of characterization techniques: ①Ni(OH) x and Ni(OH) x -Ru NC The corresponding XRD patterns of the samples are as follows: Figure 2 As shown. After Ru treatment, Ni(OH) x -Ru NC The diffraction peaks of the catalyst still largely coincide with the positions of Ni(OH)₂·0.75H₂O (JCPDS no. 00-038-0715). ② For example Figure 3 EPR spectrum analysis of the catalyst showed that the catalytic hydrogen peroxide was mainly composed of ·OH and O2. ·- A secondary catalytic process. ③ X-ray absorption spectroscopy (XAS) reveals the prepared Ni(OH) x -Ru NC The coordination environment of Ru in the sample. Ni(OH) x -Ru NC The Ru K-edge X-ray absorption near-edge (XANES) spectrum shows that the energy of the adsorption edge is between that of Ru foil and RuO, indicating that Ni(OH) x -Ru NC There is a positively charged Ru ( Figure 4 -A). Figure 4 -B indicates Ni(OH) x -Ru NCFourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum of Ru K-edge in the sample. The scattering peak at that location is assigned to the Ru-O contribution. The main peak at this location is attributed to the Ru-Ru contribution from the Ru cluster. ④Ni(OH) x -Ru NC Wavelet transform (WT) analysis in approximately and There are two maximum intensities, assigned to Ru-O and Ru-Ru respectively, with Ru-Ru having a higher intensity than Ru-O. Figure 5 ).

[0011] To quantify the catalytic performance of catalysts, UV-Vis absorption spectroscopy analysis and kinetic experiments at different concentrations were performed using TMB and H2O2 as substrates to obtain the Km value in the Michaelis-Menten equation, thus providing a direct representation of the catalyst's activity. For example... Figure 6 , 7 Data from 8 shows that 5 μg·mL -1 Ni(OH) x -Ru NC The maximum reaction rate (V) of the catalytic substrate H2O2 max The value is 1047.4 × 10 -8 M·s -1 K m The maximum reaction rate (V) of the catalytic substrate TMB was 1995 mM. max The value is 69.32 × 10 -8 M·s -1 K m The concentration was 0.213 mM. Simultaneously, to investigate the optimal catalytic conditions, different reaction temperatures and pH values ​​were established, and the TMB colorimetric intensity was measured to determine the optimal reaction conditions. For example... Figure 9 The results showed that the optimal temperature for the catalyst was 40℃ and the optimal pH was 4.5.

[0012] Compared with the prior art, the beneficial effects of the technical solution of the present invention are as follows:

[0013] 1. The Ni(OH) synthesized in this invention x -Ru NC The catalyst exhibited significantly enhanced catalytic activity. (5 μg·mL) -1 Ni(OH) x -Ru NC The maximum reaction rate (V) of the catalytic substrate H2O2 max The value is 1047.4 × 10 -8 M·s -1 K mThe maximum reaction rate (V) of the catalytic substrate TMB was 1995 mM. max The value is 69.32 × 10 -8 M·s -1 K m The concentration is 0.213 mM. This high catalytic efficiency makes it a promising candidate for applications in biosensing, environmental remediation, and chemical synthesis. It can significantly improve reaction efficiency, reduce catalyst usage, and thus save costs.

[0014] 2. The Ni(OH) provided by this invention x -Ru NC The synthesis method is mild, requiring only a reaction temperature of 120°C, making it suitable for most conventional laboratory environments and reducing equipment requirements and energy consumption. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the process for preparing the ruthenium-based catalyst of the present invention;

[0016] Figure 2 These are XRD images of the nanomaterials prepared in specific embodiments 1 and 2 of this invention;

[0017] Figure 3 The EPR spectrum (A: O2) of the nanomaterials prepared in specific embodiment 2 of the present invention is shown below. ·- B: 1 O2, C:·OH);

[0018] Figure 4 The XANES spectrum (A), FT-EXAFS spectrum (B), and extended edge fitting (C) of the nanomaterials prepared in Specific Embodiment 2 of the present invention are shown.

[0019] Figure 5 This is a wavelet transform diagram of the nanomaterials prepared in specific embodiment 2 of the present invention;

[0020] Figure 6 This is the ultraviolet-visible absorption spectrum of specific embodiment 3 of the present invention;

[0021] Figure 7 Michaelis-Menten kinetic analysis (A) and Lineweaver-Burk plot (B) were performed on the nanomaterials prepared in Specific Example 2 of this invention with different concentrations of TMB.

[0022] Figure 8 Michaelis-Menten kinetic analysis (A) and Lineweaver-Burk plot (B) were performed on the nanomaterials prepared in Specific Example 2 of this invention with different concentrations of H2O2.

[0023] Figure 9 The optimization of catalytic conditions for the nanomaterials prepared in Specific Example 2 of the present invention includes (A) pH value and (B) temperature. Detailed Implementation

[0024] To make the technical problems solved by this invention, the technical solutions adopted, and the technical effects achieved clearer, the technical solutions of the embodiments of this invention will be described in further detail below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Specific Implementation Example 1:

[0026] 1. Dissolve 725 mg Ni(NO3)2·6H2O in a mixed solution containing 10 mL deionized water and 20 mL triethylene glycol;

[0027] 2. After a clear solution is formed, it is added to 10 mL of aqueous solution containing 300 mg urea, 126 mg NaHCO3 and 2 mL tetrabutylammonium hydroxide (TBAH, 25% aqueous solution). After stirring vigorously for 15 minutes, the mixed solution is transferred to a 50 mL Teflon autoclave and reacted at 120 °C for 12 h.

[0028] 3. Wash three times with deionized water and ethanol respectively, and dry in a vacuum oven at 60℃. The resulting powder is Ni(OH). x Nanoplate; Specific Implementation Example 2:

[0030] 1. Dissolve 725 mg Ni(NO3)2·6H2O in a mixed solution containing 10 mL deionized water and 20 mL triethylene glycol;

[0031] 2. After a clear solution is formed, it is added to 10 mL of aqueous solution containing 300 mg urea, 126 mg NaHCO3 and 2 mL tetrabutylammonium hydroxide (TBAH, 25% aqueous solution). After stirring vigorously for 15 minutes, the mixed solution is transferred to a 50 mL Teflon autoclave and reacted at 120 °C for 12 h.

[0032] 3. Wash three times with deionized water and ethanol respectively, and dry in a vacuum oven at 60℃. The resulting powder is Ni(OH). x Nanoplate;

[0033] 4. Add 50mg Ni(OH) x Suspended in a mixed solution containing 10 mL of deionized water and 5 mL of methanol;

[0034] 5. Add 15 mg of RuCl3·3H2O, degas the solution with nitrogen for 30 minutes, irradiate under ultraviolet light for 3 hours, wash with water 3 times, and freeze-dry for 24 hours to obtain Ni(OH). x -Ru NC powder. Specific Implementation Example 3:

[0036] 1. Accurately weigh 5 mg of Ni(OH) in Specific Example 2. x -Ru NC The powder was dissolved in 0.5 mL of deionized water and shaken to mix, yielding a 10 mg / mL Ni(OH) solution. x -Ru NC suspension;

[0037] 2. Accurately weigh 240 mg of tetramethylbenzidine (TMB) and dissolve it in 10 mL of DMSO / ddH2O = 1 / 9 to obtain 100 mL of TMB solution;

[0038] 3. Prepare ① 100 μL acetate buffer, ② 10 μL 100 mM TMB, 90 μL acetate buffer, ③ 1 μL 10 M H₂O₂, 10 μL 100 mM TMB, 89 μL acetate buffer, and ④ 10 μL Ni(OH)₂. x -Ru NC Suspension, 90 μL acetate buffer, ⑤ 10 μL Ni(OH)₂ x -Ru NC Suspension, 10 μL 100 mM TMB, 80 μL acetate buffer, ⑥ 10 μL Ni(OH)₂ x -Ru NC Suspension, 1 μL 10M H₂O₂, 89 μL acetate buffer, 10 μL Ni(OH)₂ x -Ru NC The suspension was mixed with 1 μL of 10M H2O2, 10 μL of 100mM TMB, and 79 μL of acetate buffer. The absorbance was then measured in the wavelength range of 500 nm to 700 nm. Specific Implementation Example 4:

[0040] 1. Accurately weigh 5 mg of Ni(OH) in Specific Example 2. x -Ru NC The powder was dissolved in 0.5 mL of deionized water and shaken to mix, yielding a 10 mg / mL Ni(OH) solution. x -Ru NC suspension;

[0041] 2. Accurately weigh 240 mg of tetramethylbenzidine (TMB) and dissolve it in 10 mL of DMSO / ddH2O = 1 / 9 to obtain 100 mL of TMB solution;

[0042] 3. Add 1 μL of Ni(OH) x -Ru NC The suspension was reacted with 1 μL of 10M H₂O₂, 2.5 μL of 100mM TMB, and 95.5 μL of acetate buffer to produce a 0.1 mg / mL Ni(OH)₂ solution. x -Ru NC The absorbance of 2.5 mM TMB was measured at 652 nm for 300 s using 0.1 M H2O2.

[0043] 4. The specific steps are basically the same as in step 3, except that the TMB volume is 4ul and the acetate buffer volume is 94ul;

[0044] 5. The specific steps are basically the same as in step 3, except that the TMB volume is 5ul and the acetate buffer volume is 93ul;

[0045] 6. The specific steps are basically the same as in step 3, except that the TMB volume is 7.5 μL and the acetate buffer volume is 90.5 μL;

[0046] 7. The specific steps are basically the same as in step 3, except that the TMB volume is 10ul and the acetate buffer volume is 88ul;

[0047] 8. The specific steps are basically the same as in step 3, except that the TMB volume is 20ul and the acetate buffer volume is 78ul;

[0048] 9. The specific steps are basically the same as in step 3, except that the TMB volume is 40ul and the acetate buffer volume is 58ul. Specific Implementation Example 5:

[0050] 1. Accurately weigh 5 mg of Ni(OH) in Specific Example 2. x -Ru NC The powder was dissolved in 0.5 mL of deionized water and shaken to mix, yielding a 10 mg / mL Ni(OH) solution. x -Ru NC suspension;

[0051] 2. Accurately weigh 240 mg of tetramethylbenzidine (TMB) and dissolve it in 10 mL of DMSO / ddH2O = 1 / 9 to obtain 100 mL of TMB solution;

[0052] 3. Add 1 μL of Ni(OH) x -Ru NC The suspension was reacted with 0.5 μL of 10 M H₂O₂, 10 μL of 100 mM TMB, and 88.5 μL of acetate buffer to produce a Ni(OH)₂ concentration of 0.1 mg / mL. x -RuNC The absorbance of 10 mM TMB was measured at 652 nm for 300 s using 0.05 M H2O2.

[0053] 4. The specific steps are basically the same as in step 3, except that the volume of H2O2 is 0.75ul and the volume of acetate buffer is 88.25ul;

[0054] 5. The specific steps are basically the same as in step 3, except that the volume of H2O2 is 1 μL and the volume of acetate buffer is 88 μL;

[0055] 6. The specific steps are basically the same as in step 3, except that the volume of H2O2 is 1.25ul and the volume of acetate buffer is 87.75ul;

[0056] 7. The specific steps are basically the same as in step 3, except that the volume of H2O2 is 2.5ul and the volume of acetate buffer is 86.5ul;

[0057] 8. The specific steps are basically the same as in step 3, except that the volume of H2O2 is 3.75ul and the volume of acetate buffer is 85.25ul;

[0058] 9. The specific steps are basically the same as step 3, except that the volume of H2O2 is 5ul and the volume of acetate buffer is 84ul. Specific Implementation Example 6:

[0060] 1. Accurately weigh 5 mg of Ni(OH) in Specific Example 2. x -Ru NC The powder was dissolved in 0.5 mL of deionized water and shaken to mix, yielding a 10 mg / mL Ni(OH) solution. x -Ru NC suspension;

[0061] 2. Accurately weigh 240 mg of tetramethylbenzidine (TMB) and dissolve it in 10 mL of DMSO / ddH2O = 1 / 9 to obtain 100 mL of TMB solution;

[0062] 3. Add 1 μL of Ni(OH) x -Ru NC The suspension was mixed with 0.5 μL of 10 M H₂O₂, 10 μL of 100 mM TMB, and 88.5 μL of acetate buffer (pH 4.5). After reacting at 16 °C, the absorbance was measured at 652 nm.

[0063] 4. The specific steps are basically the same as in step 3, except that the reaction temperature is 25℃;

[0064] 5. The specific steps are basically the same as in step 3, except that the reaction temperature is 37℃;

[0065] 6. The specific steps are basically the same as in step 3, except that the reaction temperature is 40℃;

[0066] 7. The specific steps are basically the same as in step 3, except that the reaction temperature is 42℃;

[0067] 8. The specific steps are basically the same as in step 3, except that the reaction temperature is 50℃.

[0068] Specific Example 7 is basically the same as Specific Example 6, except that the reaction temperature is 37°C and the pH of the acetate buffer is 3.6, 3.8, 4.0, 4.5, 5.0 and 5.6.

[0069] The foregoing has provided a detailed description of a ruthenium-based catalyst with high catalytic activity and its preparation method. The above description, in conjunction with specific preferred embodiments, further illustrates the present invention and should not be construed as limiting the specific implementation of the invention to these descriptions. For those skilled in the art, the structural form of this invention can be flexibly varied without departing from its concept, and a series of products can be derived. Any simple deductions or substitutions should be considered as falling within the patent protection scope defined by the submitted claims.

Claims

1. A ruthenium-based catalyst with high catalytic activity and its preparation method, characterized in that, Ruthenium (Ru) clusters are highly dispersed and stably supported on a nickel hydroxide carrier (Ni(OH)). x -Ru NC ); Wherein, the Ni(OH) x -Ru NC The preparation steps are as follows: (1) Dissolve nickel nitrate hexahydrate in a mixed solution containing triethylene glycol and water to obtain a nickel nitrate solution; (2) The aqueous solution containing urea, sodium bicarbonate and tetrabutylammonium hydroxide is stirred and mixed with the nickel nitrate solution, transferred to a Teflon autoclave, reacted at high temperature, and washed and dried to obtain powdered nickel hydroxide nanoplates. (3) The nickel hydroxide nanoplates are suspended in a mixed solution containing methanol and water to obtain a nickel hydroxide suspension; (4) After dissolving ruthenium trichloride trihydrate powder, the solution was degassed with nitrogen and irradiated with ultraviolet light for 3 hours. After washing, the solution was freeze-dried to obtain Ni(OH). x -Ru NC .

2. The mixed solution in step (1) of claim 1 is 10 ml of deionized water and 20 ml of triethylene glycol.

3. The tetrabutylammonium hydroxide (TBAH) mentioned in step (2) of claim 1 is a 25% aqueous solution, and the reaction is carried out in a Teflon autoclave at 120°C for 12 hours.

4. The mixed solution in step (3) of claim 1 is 10 ml of deionized water and 5 ml of methanol.

5. Ni(OH) prepared according to claim 1 x -Ru NC Its characteristics are, Excellent peroxidase activity: 5 μg·mL - 1 Ni(OH) x -Ru NC The maximum reaction rate (V) of the catalytic substrate H2O2 max The value is 1047.4 × 10 -8 M·s -1 K m The maximum reaction rate (V) of the catalytic substrate TMB was 1995 mM. max The value is 69.32 × 10 -8 M·s -1 K m It is 0.213mM.

6. Ni(OH) prepared according to claim 1 x -Ru NC Its characteristics are, The optimal conditions are 40℃ and pH 4.5.